Deleterious variants in TAF7L cause human oligoasthenoteratozoospermia and its impairing histone to protamine exchange inducing reduced in vitro fertilization - Bai, Haowei; Sha, Yanwei; Tan, Yueqiu; Li, Peng; Zhang, Yuxiang; Xu, Junwei; Xu, Shuai; Ji, Zhiyong; Wang, Xiaobo; Chen, Wei; Zhang, Jianxiong; Yao, Chencheng; et al. (Frontiers in Endocrinology, 2023)
Introduction Oligoasthenoteratozoospermia (OAT) is a major cause of infertility in males. Only a few pathogenic genes of OAT have been clearly identified till now. A large number of OAT-affected cases remain largely unknown. Methods Here, Whole-exome sequencing (WES) in 725 idiopathic OAT patients was performed. Ejaculated spermatozoa by OAT patients were microinjected into mouse oocytes to estimate fertilization potential. Diff-quick staining and transmission electron microscopy were performed to evaluate sperm morphology and ultrastructure. The protein expression level and localization In vitro were detected by Western Blotting and Immunocytochemistry. Results We identified four X-linked hemizygous deleterious variants of TAF7L—namely, c.1301_1302del;(p.V434Afs*5), c.699G>T;(p.R233S), c.508delA; (p. T170fs), c.719dupA;(p.K240fs) —in five probands. Intracytoplasmic sperm injection (ICSI) were carried out in M1, M2-1and M3 patient's wife. However only M1 patient’s wife became pregnant after embryo transfer. In vitro study demonstrated significantly reduced fertilization ability in patient with TAF7L mutation. The TAF7L mutation let to abnormal sperm head and impaired histone-to protamine exchange. Variant 719dupA (p. K240fs) resulted in producing a truncated TAF7L protein and localized massively within the nucleus. In addition, TAF7L expression were not able to be detected due to variants c.1301_1302del (p. V434Afs*5) and c.508delA (p. T170fs) In vitro. Conclusion Our findings support that TAF7L is one of pathogenic genes of OAT and deleterious mutations in TAF7L may cause impaired histone-to-protamine affected the chromatin compaction of sperm head.